Inhibitory effects of vaginal Lactobacilli on Candida albicans growth, hyphal formation, biofilm development, and epithelial cell adhesion - Takano, Tomonori; Kudo, Hayami; Eguchi, Shuhei; Matsumoto, Asami; Oka, Kentaro; Yamasaki, Yukitaka; Takahashi, Motomichi; Koshikawa, Takuro; Takemura, Hiromu; Yamagishi, Yuka; Mikamo, Hiroshige; Kunishima, Hiroyuki (Frontiers in Cellular and Infection Microbiology, 2023)
Antifungal agents are not always efficient in resolving vulvovaginal candidiasis (VVC), a common genital infection caused by the overgrowth of Candida spp., including Candida albicans, or in preventing recurrent infections. Although lactobacilli (which are dominant microorganisms constituting healthy human vaginal microbiota) are important barriers against VVC, the Lactobacillus metabolite concentration needed to suppress VVC is unknown. Therefore, we quantitatively evaluated Lactobacillus metabolite concentrations to determine their effect on Candida spp., including 27 vaginal strains of Lactobacillus crispatus, L. jensenii, L. gasseri, Lacticaseibacillus rhamnosus, and Limosilactobacillus vaginalis, with inhibitory abilities against biofilms of C. albicans clinical isolates. Lactobacillus culture supernatants suppressed viable bacteria by approximately 24%-92% relative to preformed C. albicans biofilms; however, their suppression differed among strains and not species. Lactate production was necessary to suppress preformed biofilms and C. albicans hyphal elongation, whereas hydrogen peroxide was not always essential. Both lactate and hydrogen peroxide were required to suppress C. albicans planktonic cell growth. Lactobacillus strains that significantly inhibited biofilm formation in culture supernatant also inhibited C. albicans adhesion to epithelial cells in an actual live bacterial adhesion competition test. Healthy human microflora and their metabolites may play important roles in the development of new antifungal agent against C. albicans-induced VVC.